Family-Based Health Insurance for Informal Sector Workers in Vietnam: Why Does Enrolment Remain Low?. (November 2018) - Thi Thuy Nga, Nguyen; FitzGerald, Gerard; Dunne, Michael
Providing financial protection to the whole population is a top health policy priority of many countries. However, expanding social health insurance coverage to the "informal sector worker" is a challenge in many developing countries. This study analyzed the reasons for the limited coverage of health insurance for informal sector workers. Direct interviews were carried out with 391 uninsured households in Vietnam, followed by in-depth interviews with 11 key stakeholders. The study offers several possible explanations for the low enrollment in family-based health insurance scheme at both the demand and supply sides, such as inability to pay the premium, lack of information, perceived poor quality of primary health care services, and complicated enrollment procedures. The study suggests that a partial government subsidy and improvement in the quality of primary health care are crucial strategies for health insurance expansion for the informal sector workers and their families.